Gynaecological Cancers in Surgical Specimens A Hospital Based Analysis (Medicine Today, 2015)
Female genital tract malignancies have worldwide distribution, but the distribution and frequency vary from one region to another. The preventable carcinoma of the cervix is still the leading cause of cancer morbidity and mortality in the developing countries. Objective of this study is to determine the patterns and frequency of female genital tract malignancies in our population and to compare it with other national and international studies. A six-year retrospective analysis of histopathologically proven gynecological malignancies was performed in the Department of Pathology, Enam Medical College & Hospital, Savar between January 2008 and December 2013. Out of the total 185 gynaecological cancers diagnosed, 120 cases (64.87%) were cervical, 44 (23.78%) ovarian, 12 (6.49%) corpus uteri, 7 (3.78%) vulval, and 2 (1.08%) vaginal cancers. No malignant lesion is found in the myometrium and the fallopian tube. Age of the cases ranged from 4 months and 85 years with mean age 43.91±12.84 years. The mean ages of cervical and ovarian cancers were 46.64±10 and 37.16±14.66 years respectively. Majority of the patients were between the fourth and six decade with peak frequency in the fifth decade of life. Squamous cell carcinoma was the commonest histopathologic type in cervical and vulval cancers whereas serous cyst adenocarcinoma and endometrioid adenocarcinoma were the commonest types in the ovary and endometrium respectively. Carcinoma of the cervix was the commonest malignancy encountered in this study. Effective screening programs and public awareness is necessary for early diagnosis and decrease mortality.Medicine Today 2014 Vol.26(2): 78-82